KECEMASAN PADA REMAJA PECANDU EKSTASI - Satrio, Bagus Satrio Jiwandono; Fajar Kawuryan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Anxiety is a natural response to anticipating threats; however, when it becomes persistent, irrational, and intense, it can develop into an anxiety disorder that disrupts daily activities. Anxiety among adolescents, particularly drug addicts like ecstasy users, is a significant concern due to its impact on quality of life, health, interpersonal relationships, education, productivity, and healthcare costs. This study aims to analyze aspects of anxiety in adolescent ecstasy users in Kudus City through a qualitative phenomenological approach, employing observation and interviews, with data analyzed using coding and triangulation. The findings reveal that all three informants exhibited symptoms of anxiety disorders in physical, cognitive, behavioral, and emotional aspects, as well as tendencies toward social anxiety. For example, Informant 1 felt fearful upon hearing a motorbike in front of their house, assuming it was the police. Meanwhile, Informants 2 and 3 withdrew from social interactions, feared meeting new people, and experienced difficulty speaking. All three preferred spending time alone in their rooms.